2014
DOI: 10.1186/1471-2334-14-53
|View full text |Cite
|
Sign up to set email alerts
|

A metabolic biosignature of early response to anti-tuberculosis treatment

Abstract: BackgroundThe successful treatment of tuberculosis (TB) requires long-term multidrug chemotherapy. Clinical trials to evaluate new drugs and regimens for TB treatment are protracted due to the slow clearance of Mycobacterium tuberculosis (Mtb) infection and the lack of early biomarkers to predict treatment outcome. Advancements in the field of metabolomics make it possible to identify metabolic profiles that correlate with disease states or successful chemotherapy. However, proof-of-concept of this approach ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
71
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(73 citation statements)
references
References 43 publications
(42 reference statements)
2
71
0
Order By: Relevance
“…Although metabolomic approaches will be discussed in detail in a separate article, it is nevertheless important to note that biosignatures of small-molecule molecular features (MFs) have been identified in urine sample of TB patients using mass spectrometry (Mahapatra et al 2014). In these samples, levels of 45 MFs changed significantly by month 1 of anti-TB treatment, with levels of 23 MFs consistently changing in abundance until the end of treatment (Mahapatra et al 2014). This approach of identifying urine-based anti-TB treatment response biosignatures serves as proof of concept for further metabolomics investigations.…”
Section: Untargeted Approaches and New Technologiesmentioning
confidence: 99%
“…Although metabolomic approaches will be discussed in detail in a separate article, it is nevertheless important to note that biosignatures of small-molecule molecular features (MFs) have been identified in urine sample of TB patients using mass spectrometry (Mahapatra et al 2014). In these samples, levels of 45 MFs changed significantly by month 1 of anti-TB treatment, with levels of 23 MFs consistently changing in abundance until the end of treatment (Mahapatra et al 2014). This approach of identifying urine-based anti-TB treatment response biosignatures serves as proof of concept for further metabolomics investigations.…”
Section: Untargeted Approaches and New Technologiesmentioning
confidence: 99%
“…We also recently identified extracellular metabolites specific to M. tuberculosis (25), supporting the potential of metabolomics in exploring novel biomarkers to better understand its biology and pathogenesis. On the other hand, metabolomics applied on direct patient samples may reveal specific diagnostic markers or be used to monitor treatment response (26)(27)(28)(29). It has been shown that volatile organic compounds (VOCs) in the urine of TB patients can be distinguished from those of healthy subjects (26).…”
mentioning
confidence: 99%
“…Owing to the considerable technical challenges (Boshoff and Lun 2010), metabolomics has been most profitably applied during growth of M. tuberculosis under defined conditions in vitro (de Carvalho et al 2010a;Beste et al 2011Beste et al , 2013Watanabe et al 2011), although there is increasing use of metabolite profiling to identify biomarkers of infection in experimental models as well as clinical specimens (Shin et al 2011;du Preez and Loots 2013;Zhou et al 2013;Mahapatra et al 2014). As noted above, these techniques have proved especially useful in enabling key insights into central carbon metabolism in M. tuberculosis and, in addition to investigating known pathways, have revealed cryptic biochemical functions.…”
Section: Advances In the Postgenomic Eramentioning
confidence: 99%
“…Of special interest is the identification of kynurenine as a defining metabolite of active TB (Weiner et al 2012b), because this is the product of the indoleamine-2,3-dioxygenase-catalyzed degradation of tryptophan that, as detailed above, recent work has implicated in the host antimycobacterial response (Zhang et al 2013b). Other approaches include the analysis of sputum for both mycobacterial and host markers of disease (du Preez and Loots 2013), as well as the development of urinary metabolite signatures to track the response to chemotherapy (Mahapatra et al 2014). In addition, differential metabolite profiles have been investigated as a method to speciate pathogenic and nonpathogenic mycobacteria (Olivier and Loots 2012) and to investigate the impact of drug resistance mutations on bacterial physiology (Bisson et al 2012;Loots 2014), as discussed further below.…”
Section: Advances In the Postgenomic Eramentioning
confidence: 99%